2021
DOI: 10.1128/mra.01390-20
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Achromobacter xylosoxidans Myophage Mano

Abstract: Achromobacter spp. are ubiquitous Gram-negative bacteria, some of which can cause respiratory tract infections in patients with autoimmune disorders and cystic fibrosis. Bacteriophages have therapeutic and biotechnological potential to combat Achromobacter sp. infections. This announcement details the 42.5-kb genome sequence of the temperate Achromobacter xylosoxidans myophage Mano.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…To date, a total of 20 Achromobacter species and 24 genogroups belong to this genus [7,8]; however, knowledge on bacteriophages targeting this bacterium is still scarce. While a number of published reports of Achromobacter phages may be found in the literature [9][10][11][12][13][14][15][16][17], nearly all describe viruses that are lytic against Achromobacter xylosoxidans, the type species of the genus. To date, there have been no reports of bacteriophages active on Achromobacter spanius.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a total of 20 Achromobacter species and 24 genogroups belong to this genus [7,8]; however, knowledge on bacteriophages targeting this bacterium is still scarce. While a number of published reports of Achromobacter phages may be found in the literature [9][10][11][12][13][14][15][16][17], nearly all describe viruses that are lytic against Achromobacter xylosoxidans, the type species of the genus. To date, there have been no reports of bacteriophages active on Achromobacter spanius.…”
Section: Introductionmentioning
confidence: 99%
“…A BLAST search using sequences of Murka’s sequences indicated that Foxunavirus phages were the closest relatives. The search also found related phages infecting bacteria, other than Xanthomonas , including Burkholderia phage Mica (genus Micavirus ) [ 60 ], Achromobacter phage Mano (genus Manovirus ) [ 61 ], Acinetobacter phage Alexa (unclassified), Escherichia phage vB_EcoM-ep3 (genus Jilinvirus ) [ 62 ], and Serratia phage MQ-4 (unclassified) [ 63 ]. The results of comparative genome alignment showed a similarity of genomic organization between these phages, Foxunavirus phages, and phage Murka ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%